Development Authentication and Authorization Systems of Multi Information Systems Based REst API and Auth Token - Indra Gita Anugrah; Muhamad Aldi Rifai Imam Fakhruddin (INNOVATION RESEARCH JOURNAL, 2020)
The security of an application is the most important problem in an information system integration process. The authentication and authorization process is usually carried out using Single Sign On (SSO). Authentication and authorization methods are used to secure data in a system. The authentication and authorization processes are carried out on the client side (web browser) in the form of a session and on the server side (web server) in the form of cookies. Sessions and cookies are valuable assets in the authentication and authorization process because they contain the data required for the login process so that the session and cookies need to be secured. Session is a combination of username and password data that has been encrypted while cookies store login information data so that they are still in a state of gaining access according to the privileges given to the user. So important is the role of sessions and cookies in the authentication and authorization process, so we need a way to secure data on sessions and cookies. One way to secure data is to use the REst API and Auth Token.